Outcomes of tutorial teaching. Strategies for nursing training in the new pedagogical model. - Zulema Bos Rodríguez; Antonio Rodríguez Hernández; María Julia Placeres Hernández; Jorge Luis Maceira Brito (Medisur)
Background: Educacation at work is the main form of the educative process in the clinical cycle of the medical higher educational system which the superior form is the tutorial one. Objective: To evaluate the strategy applied in the tutorial in the nursing new pedagogical model. Methods: A descriptive study of intervention and evaluation which started in the 1st academic year on September, 2004 collecting the application and evaluation of the strategy applied in the tutorial process of the nursing new pedagogical model. 163 students of the 2nd academic year of the Bachellor of Science in Nursing were the universe of this investigation. 50 % of them were taken as a randomized sample from 82 groups. Differente documents were reviewed and a survey was applied in order to evaluate the strategy according to the attention received by their tutors and the mark obtained in the practical final exam of 1st and 2nd academic year of their study. Results: Strategies were evaluated as Good taking into consideration the criterion of the managers of the hospital institution and the personnel in charge of the educative process. All the students passed the practical final exam and there was a predominium of the highest mark (5). The majority of the students consider the attention given by their tutors as Good. The results in the final exams in both courses behaved in a similar way with a slight augmentation in the highest category (5) in the academic course 2004-2005.